2000
DOI: 10.1523/jneurosci.20-24-09162.2000
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning an Auditory Synapse for Speed and Fidelity: Developmental Changes in Presynaptic Waveform, EPSC Kinetics, and Synaptic Plasticity

Abstract: Fast, precise, and sustained synaptic transmission at high frequency is thought to be crucial for the task of sound localization in the auditory brainstem. However, recordings from the calyx of Held synapse have revealed severe frequency-dependent synaptic depression, which tends to degrade the exact timing of postsynaptic spikes. Here we investigate the functional changes occurring throughout the critical period of synapse refinement from immature calyx terminal [postnatal day 5 (P5)] to after the onset of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

94
577
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(677 citation statements)
references
References 70 publications
(97 reference statements)
94
577
6
Order By: Relevance
“…1 A). We confirmed that the AP waveform of P8 -P12 calyces showed slower rise and repolarization times as well as wider width than that of P16 -P18 calyces, as reported previously for the developing calyx of Held synapse in rat (Taschenberger and von Gersdorff, 2000;von Gersdorff and Borst, 2002). Subsequently, we used these waveforms as command templates to perform voltage-clamp recordings of presynaptic Ca 2ϩ currents (see Materials and Methods) paired simultaneously with recordings of EPSCs in 1 mM extracellular Ca 2ϩ , which is near the physiological concentration of Ca 2ϩ in the brain fluid (Jones and Keep, 1988).…”
Section: Developmental Difference In Action Potential-evoked Release supporting
confidence: 91%
“…1 A). We confirmed that the AP waveform of P8 -P12 calyces showed slower rise and repolarization times as well as wider width than that of P16 -P18 calyces, as reported previously for the developing calyx of Held synapse in rat (Taschenberger and von Gersdorff, 2000;von Gersdorff and Borst, 2002). Subsequently, we used these waveforms as command templates to perform voltage-clamp recordings of presynaptic Ca 2ϩ currents (see Materials and Methods) paired simultaneously with recordings of EPSCs in 1 mM extracellular Ca 2ϩ , which is near the physiological concentration of Ca 2ϩ in the brain fluid (Jones and Keep, 1988).…”
Section: Developmental Difference In Action Potential-evoked Release supporting
confidence: 91%
“…Many parameters of synaptic transmission are quite variable from calyx to calyx at this developmental stage. Examples of such parameters include decay of residual Ca 2ϩ and facilitation (Felmy et al 2003), reliability in following high-frequency trains (Taschenberger et al 2002), rate of depression following such trains (von Gersdorff et al 1997), and recovery from this depression (unpublished results). If the combined influence of multiple inputs is measured, the results will be different from those expected for a single input as shown for depression and recovery from depression in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The mean amplitude of NMDA EPSCs in calicine terminals in the mouse medial nucleus of the trapezoid body (MNTB) decreases in a stepwise fashion between P5 and P13, whereas the mean amplitude of AMPA EPSCs increases steadily from P5 to P15 (Futai et al, 2001;Joshi and Wang, 2002;Youssoufian et al, 2005). In rat MNTB, AMPA receptor-mediated EPSCs as well as quantal synaptic currents acquire progressively faster kinetics, whereas NMDAR-mediated EPSCs diminish with age, as indicated by a 50% reduction in mean amplitude and faster decay kinetics from P5 to P14 (Taschenberger and von Gersdorff, 2000). The mean conductance of both spontaneous and evoked NMDA-EPSCs in the endbulb-bushy cell synapse decreased by more than half between P4-11 and P12-22 (Isaacson and Walmsley, 1995;Bellingham et al, 1998).…”
Section: Glutamate Receptors In Mammalian and Avian Auditory Developmentmentioning
confidence: 99%